Transit of materiality: The flow of aesthetically expressive practices between book and television – an investigation about Mad Maria - Wajnman, Solange (2018)
Upon primarily investigating the literary transposition of the historical novel Mad Maria to television format, but also taking in account the examples of the novels O primo Basílio and Os Maias, that also were adapted into miniseries, proposes a theorical-methodological approach, under the vision of materialities study in the field of audiovisual. Inside this context, it’s argued that the language used on the miniserie Mad Maria selected and amplified certain thematic aspects of the original romance in detriment of the adequation for television format, and has yet made able a series of hybridization resources among the different formats that would not be applicable inside the paradigm of intertextuality and culture of the book.